Mean Differences of Total Cholesterol Levels among Vegetarians and Non-Vegetarians at Maha Vihara Maitreya Duta Palembang, Indonesia - Nudhar, Lathifah; Subandrate, Subandrate; Susilawati, Susilawati; Oswari, Liniyanti (Folia Medica Indonesiana, 2020)
Total cholesterol level is one of the risk factor of cardiovascular disease. The proportion rate of hypercholesterolemia in Indonesia remains high, numbering around one third of (35,9%) Indonesians. Hypercholesterolemia is a modifiable risk factor, one of early measures that can be taken to prevent hypercholesterolemia is nutritional intervention. A dietary pattern high in plant sources and lower fat consumption has been recommended by several health organisation for prevention of hypercholesterolemia. This study was intended to determine mean difference of cholesterol level between vegetarian and nonvegetarian in Maha Vihara Maitreya Duta Palembang. This was an observational analytical study with cross-sectional design. A total of 173 subjects at Maha Vihara Maitreya Duta Palembang was included which consist of 80 Vegetarian and 93 Nonvegetarian. Measurement of total cholesterol level was done using rapid diagnostic test (RDT) Autocheck® Multi Monitoring System and parametric Independent T Test was chosen as method of statistical analysis. p <0.001 indicates significant differences of total cholesterol level between vegetarian (172,51± 39,05 mg/dL ) and nonvegetarian (228,67±68,07 mg/dL) groups. The mean differences of total cholesterol of vegetarian group is 56,16 mg/dl lower than non vegetarian groups. A significant differences exist in total cholesterol level between vegetarian and non vegetarian group at Maha Vihara Maitreya Duta Palembang. Vegetarian groups has lower total cholesterol level compared to nonvegetarian.